Contextualizing Management Research: An Open Systems Perspective. (5th September 2021) - Filatotchev, Igor; Ireland, R. Duane; Stahl, Günter K.
Abstract: Management researchers rely frequently on theoretical perspectives originating in North American and European contexts. Given the influences context has on scholarship, the question becomes if using primarily Western theories provides researchers with the design insights needed to capture the robust context of the setting in which they conduct their studies. Herein, we seek to establish a foundation for developing fertile exchanges of ideas regarding contextualized management research. To do this, we examine some of the main theories in management studies through the heuristic lens of an 'open systems' framework that allows us to build on comparative management and institutional theories. We discuss existing theory advances in selected areas of management studies, including corporate governance, strategic management, entrepreneurship, and corporate social responsibility (CSR) to offer avenues for future research. Completing studies with a solid grounding in contextualized management theories has the potential to provide novel research avenues and opportunities to integrate diverse theoretical perspectives. We also identify a need for multidisciplinary research, epistemological openness, and methodological pluralism.